Covering the scandal in 140 characters : a case study of Twitter's role in coverage of the Penn State saga - Sanderson, Jimmy; Hambrick, Marion E. (London : Human Kinetics, Inc., 2012)
This case study explored how sports journalists used Twitter to cover allegations about former Penn State University assistant football coach Jerry Sandusky sexually abusing young boys. A content analysis of 1652 tweets from 151 sports journalists was conducted. Analysis revealed that sports journalists used Twitter in the following ways: a) offering commentary, b) breaking news, c) interactivity, d) linking to content, and e) promotion. The results suggest that Twitter serves as an additional venue for sports journalists to frame stories; however, their behavior in this venue blurs professional and personal boundaries as they mock fans and promote their competitors. The analysis further suggests that the immediacy with which news breaks on Twitter places sports journalists and sports media organizations into a dialectic between "being first" and "being accurate" when reporting news.
Originally published in Sanderson, J., & Hambrick, M. E. (2012). Covering the scandal in 140 characters: A case study of Twitter's role in coverage of the Penn State saga. International Journal of Sport Communication, 5(3), 384-402. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Pennsylvania State University; Twitter; Sports journalism; Social media